Burden on the Environment and Environmental Protection Expenditures in EU Countries - Maciej OESTERREICH; Emilia BAREJ-KACZMAREK (Communications of International Proceedings, 2021)
The main objective of the study was to analyse the degree of environmental burden and its impact on the level of related expenditures of EU member states. Due to the availability of data and the desire to ensure the highest possible degree of comparability, the data on 14 environmental variables from 2018 published in the Eurostat database were used. They were used to build two non-pattern taxonomic synthetic measures. The analyses in the paper show that there is no clear relationship between generated pollution and environmental expenditures; however, there is a difference between the "old" and "new" member states in this regard. The first group of countries tries to compensate for the negative impact of their economies and society on the natural environment by allocating more funds to its protection. These activities are not yet visible in the case of the countries that joined the EU after 2004.
Keywords: Environmental Protection Expenditures; EU Countries; Taxonomic Synthetic Measures